Pengaruh Variasi Nilai mA (Mili Ampere) dan s (Second) yang Berbeda Dengan Nilai mAs yang Sama Terhadap Paparan Medik yang Diterima Pasien - Maritje S. J. Malisngorar; Ira Sandi Tunny; Amelia Niwele; Akhmadi Akhmadi; Rini Hatma Rusli; Iksan Soumena; Bambang Ariyanto (Jurnal Sains dan Kesehatan, 2022)
This study aims to find out how to measure exposure dose medical techniques which accepted the patients with a variety of ma and s at the same mas value and the effect of variations in the value of mili ampere and second different with the same mas value to medical exposure dose received by patients. This type of study is an observational descriptive with the approach of the experimental or trial. using gauges medic exposure dose, x-ray multimeter with research indicator mili ampere and second are different but the same mas. From these results it can be concluded the highest medical exposure dose received by patients is the variation of 200 ma and 0.05 s with a dose value of 5.533 mgy / s. this is due to the amount of flow tube (ma). it can be concluded that the greater ma is used, the greater the dose the patient received medical.